ANALYSIS OF THE INCOME OF COCOA FARMERS IN BAMBAPUN VILLAGE, DONDO DISTRICT, TOLITOLI REGENCY: ANALISIS PENDAPATAN PETANI KAKAO DI DESA BAMBAPUN, DISTRIK DONDO, KABUPATEN TOLITOLI - Paisal Paisal; Edi Yanto (STIE MUJAHIDIN TOLITOLI, 2024)
This study aims to determine the income of cocoa farmers in Bambapun Village, Dondo District, Tolitoli Regency. This type of research is quantitative descriptive, with a survey conducted by questioning 20 cocoa farmers from various backgrounds, such as gender, age, education level, then the responses are processed and analyzed. The results of this study show that the average total cost incurred by cocoa farmers for each cocoa harvest period with a land area of 1 ha is Rp 1,8934,500. The average revenue obtained by cocoa farmers is Rp 4,992,750. And it is known that the average income of cocoa farmers is Rp 3,098,250 in one harvest period. This means that cocoa farmers still benefit from cocoa crop agricultural products.